Balancing Justice and Stability in Liberia: Implementing Transitional Justice in a Fragile Society Facing Socio-Economic Issues - Gross, Adama Aloysious Gross; Aina, Ayandiji Daniel Aina; Nwoadike, Chibuzor A. Nwoadike (African Journal of Stability and Development (AJSD), 2025)
The purpose of this study is to examined the balance between seeking justice and maintaining stability in post-conflict Liberia, that is fragile and has many socio-economic issues. The study employed a mixed-methods with convergent parallel design. The 399 respondents sample for quantitative data had a 100% response rate. Ten participants were interviewed for qualitative data. Stratified proportional sampling was used for quantitative data, whereas purposive and snowball methods were used for qualitative data. Findings from the inferential statistics showed that Economic Security has a strong positive effect on the dependent variable, Transitional Justice, explaining 61.7% of the variance (R² = 0.617, p < 0.001), with a significant standardised coefficient (β = 0.444, p < 0.001). The findings from the qualitative data showed that the most significant hindrances to the pursuit of transitional justice in Liberia include political will, finance, corruption, and inadequacies in the justice system. Threat of instability, economic hardship, and political convenience deprioritised justice, leaving victims bereft of redress. For the achievement of sustainable peace and the consolidation of democracy, Liberia must pursue a balanced approach that unites both reconciliation and justice.